Effect of different drying treatments on colour quality and ascorbic acid concentration of guava fruit - Ali, M. A.; Yusof, Yus Aniza; Chin, Nyuk Ling; Ibrahim, M. N. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Guava (Psidium guajava L.) is a rich source of vitamin C (ascorbic acid) having high water content (above 80%) which makes it extremely perishable, but storage, handling, processing and transporting becomes difficult due to high moisture content. Therefore, guava needs dehydration process by upholding its natural colour and minimum ascorbic acid losses. We have carried out a comprehensive study to examine the influence of different drying treatments; under direct sunlight, freezing, convection oven (50, 60, 70, 80 and 90°C) and microwave oven (100, 250, 440, 600 and 1000 watts) on ascorbic acid concentration and colour quality of guava. The mean values of ascorbic acid concentration of dried guava slices were changed significantly (P < 0.05) as compared to fresh guava slices. The colour of guava slices became yellowish with an increase in temperature and power of conventional and microwave ovens, respectively. We found freeze drying as the best method for the dehydration of guava in terms of ascorbic acid and natural colour preservation.